Genome Sequence of Deinococcus marmoris PAMC 26562 Isolated from Antarctic Lichen - Kim, Junghee (Genome Announc, 2017)
Deinococcus marmoris strain PAMC 26562 was isolated from Usnea sp., a lichen collected from King George Island, Antarctica. We report here the draft genome sequence of strain PAMC 26562, which has xanthorhodopsin and carbon monoxide dehydrogenase genes in addition to major metabolic pathways presented in deinococcal genomes.